(untitled) (Journal of Universal Science Research, 2023)
This study examines a problem that arises from the incompatibility of two factors. The first is the desire to improve the enterprise in accordance with the concept of Industry 4.0. And the second is the lack of sufficient material resources due to the high cost of purchasing new equipment that will meet the requirements of Industry 4.0. In this article, to solve the problem of modernizing enterprise equipment, it is proposed to create a monitoring system. The development of the system architecture is considered. Hardware complex development on the Arduino platform is also given.